2014
DOI: 10.1121/1.4895014
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of time-compressed speech does not predict recognition of natural fast-rate speech by older listeners

Abstract: This study investigated whether recognition of time-compressed speech predicts recognition of natural fast-rate speech, and whether this relationship is influenced by listener age. High and low context sentences were presented to younger and older normal-hearing adults at a normal speech rate, naturally fast speech rate, and fast rate implemented by time compressing the normal-rate sentences. Recognition of time-compressed sentences over-estimated recognition of natural fast sentences for both groups, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 15 publications
3
24
0
1
Order By: Relevance
“…Aylett and Turk, 2004). This effect of less clear articulation was also particularly present in the study by Gordon-Salant et al (2014), who found that older and younger adults had more difficulty with naturally produced fast speech than with artificially speeded speech. Whereas younger and older adults showed equal performance for the normal-rate speech in their study, older adults performed more poorly than younger adults both for the timecompressed and naturally fast materials (thus again showing an age  speech rate interaction).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Aylett and Turk, 2004). This effect of less clear articulation was also particularly present in the study by Gordon-Salant et al (2014), who found that older and younger adults had more difficulty with naturally produced fast speech than with artificially speeded speech. Whereas younger and older adults showed equal performance for the normal-rate speech in their study, older adults performed more poorly than younger adults both for the timecompressed and naturally fast materials (thus again showing an age  speech rate interaction).…”
Section: Discussionmentioning
confidence: 60%
“…Their results showed generally better comprehension scores for naturally speeded up or slowed down materials than for unselectively compressed/expanded speech, suggesting that artificial time compression presents a more difficult listening condition than naturally increased speech rate. In contrast, a recent study (Gordon-Salant et al, 2014) has shown that the recognition of artificially timecompressed read sentences seems to over-estimate the recognition of natural fast-rate speech (see also Janse, 2004). Gordon-Salant and colleagues found that both younger and older adults showed better sentence recognition performance for artificially speeded speech (originally read at a normal rate) than for natural fast-rate sentences read aloud by a talker at a very fast rate.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…This may have occurred because, after compression, consonant encounters practically disappear, making it difficult to discriminate (12) . The incorrect answers of the elderly may be associated with coarticulation, which produces overlapping segments of speech with consequent difficulty to reach the phonemic target (14) . It is also known that, from the age of 60, degenerative processes of normal aging arise and decrease the intelligibility of speech, especially when speech becomes faster or is spoken in another language (25) .…”
Section: Resultsmentioning
confidence: 99%
“…In the international literature, one study was found addressing the time-compressed speech test in the elderly, in which the results suggest that the elderly are at a disadvantage compared to young people to hear at faster speech rates (14) .…”
Section: Introductionmentioning
confidence: 99%